Struktur komunitas Echinodermata pada ekosistem lamun Desa Taulaa Kecamatan Bilato, Kabupaten Gorontalo - Hardiyanti Yusuf; Miftahul Khair Kadim (Depik, 2019)
Abstract.Echinodermatais playing an important role in food chains in waters ecosystem; however, there was no report on the Echinodermata structure in the seagrass ecosystem of Taulaa village, Gorontalo district. Hence, the objective of the study was toto determine the community structure of Echinoderms in the seagrass ecosystem of coastal area of Taulaa village, Bilato, Gorontalo regency. The research was conducted from January to April 2019. There were 3 observation stations chosen purposively. The sample of Echinoderms was observed at low tide using methods of quadrats and transects of 11 m. In addition, the water parameters were also measured i.e the temperature, the salinity, the pH, the water depth, the substrate and the water flow. Furthermore, diversity, dominanc and Evenness index were analyzed using software PAST 3.22. The results showed that there were 13 species of Echinoderms representing 4 classes, namely Ophiuroidea, Asteriodea, Echinodea dan Holothuroidea in which the highest total abundance was on 1st station and the lowest total abundance was on the 2nd station.The index of diversity was in the medium category, the index of domination was in the low category, the index of evenness showed an equitable distribution and the index of uniformity was very high.Keywords :Echinoderms, community, seagrass, Past 3.22Abstrak.Echinodermata memiliki peranan penting dalam rantai makanan pada ekosistem laut, namun demikian struktur komunitasnya di ekosistim lamun Desa Taulaa Kabupaten Gorontalo belum pernah dilaporkan. Oleh karena itupeneilitan ini bertujuanuntuk mengetahui struktur komunitas Echinodermata pada ekosistem lamun di wilayah pesisir Desa Taulaa, Bilato Kabupaten Gorontalo. Penelitian dilaksanakan pada bulan Januari hingga April 2019. Terdapat 3 stasiun pengamatan yang dipilih secarapurposive. Pengamatan sampel Echinodermata dilakukan pada saat surut dengan menggunakan transek kuadran 11 m. Selain itu dilakukan juga pengukuran terhadap parameter air yaitu suhu, salinitas, pH, kedalaman, substrat dan arus.Nilai indeks keanekaragaman, indeks dominansi dan indeks kemerataan dianalisismenggunakansoftwarePAST 3.22. Hasil penelitian menunjukkan sebanyak 13 spesies Echinodermata ditemukan yang mewakili 4 kelas yaitu Ophiuroidea, Asteriodea, Echinodea dan Holothuroidea dimana kelimpahan total tertinggi pada stasiun I dan terendah pada stasiun II.Indeks keanekaragaman kategori sedang, indeks dominasi rendah, indeks kemerataan menunjukkan penyebaran yang merata dan indeks keseragaman yang sangat tinggi.Kata kunci:Echinodermata, komunitas, Lamun, Past 3.22